An Overview Caring Behavior of Anesthesiologist in Spinal Anesthesia Patients at RSUD Cilacap - Alverina, Frianca; Suryani, Roro Lintang; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2024)
Background: Care becomes a phenomenon that affects how we think, feel, and relate to others, so basically care can be described as the ability to genuinely dedicate ourselves to other people, remain vigilant in supervision, have empathy for other individuals, and have a sense of compassion that is important in care practice. Important aspects faced include knowledge, learning through experience, patience, honesty, trust, humility, hope, and the ability to innovate. Failure to treat anesthetic meetings with patients can have a serious impact on the patient's experience during medical procedures. Aim: What is the description of the caring behavior of anesthesiologists in spinal anesthesia patients at Cilacap Hospital. Method: This research uses descriptive methods using cross sectional survey design approaches. The sampling technique was carried out using sequential samples with a total of 65 patients. Findings: The results of the study were based on the age of 32 respondents (49.2%), gender of 33 respondents (50.8%), and educational level of 30 respondents (46.2%). Conclusion: The conclusion was that the majority of respondents assessed that the anesthesia in the District Hospital of Cilacap behaved treating respondents, which is 61 respondents (93.8%).